The Global Attractors for Damped Generalized Coupled Nonlinear Wave Equations (Journal of Partial Differential Equations, 2002)
The existence of global attractors for the periodic initial value problem of damped generalized coupled nonlinear wave equations is proved. We also get the estimates of the upper bounds of Hausdorff and fractal dimensions for the global attractors by means of a uniformly priori estimates for time.
Keywords: Global Attractor; Hausdorff Dimension; Fractal Dimension